Taxifolin retards the d-galactose-induced aging process through inhibiting Nrf2-mediated oxidative stress and regulating the gut microbiota in mice. Issue 23 (17th November 2021) - Liu, Xing-Long; Zhao, Ying-Chun; Zhu, Hong-Yan; Wu, Ming; Zheng, Yi-Nan; Yang, Min; Cheng, Zhi-Qiang; Ding, Chuan-Bo; Liu, Wen-Cong
Abstract : Taxifolin ameliorated the aging process induced by d -Gal through regulating the Nrf2-mediated oxidative stress and PI3K/AKT-mediated apoptosis pathways and increasing the beneficial flora. Abstract : Aging and aging-related metabolic complications are global problems that seriously threaten public health. Taxifolin (TAX) is a novel health food and has been widely proved to have a variety of biological activities used in food and medicine. However, the delayed effect of TAX on the aging process has not been investigated. The purpose of this study is to explore the role of TAX as a natural active substance on aging brain tissue induced by d -galactose (d -Gal) and to determine the effect of supplementing TAX on the metabolism of the intestinal flora in aging bodies. The aging model was established by intraperitoneal injection of d -Gal (800 mg kg −1 ) once per 3 days for 12 weeks, and TAX (20 and 40 mg kg −1 ) was administered daily by oral gavage after 6 weeks of induction with d -Gal. After testing aging mice in an eight-arm maze, the results showed that TAX treatment significantly restored spatial learning and memory impairment. Moreover, long-term d -Gal treatment incited cholinergic dysfunction of aging mice, and H&E staining revealed obvious histopathological damage and structural disorder in the hippocampus of mouse brain tissue, while TAX treatment significantly reversed these changes. Importantly, supplementing with TAX significantly mitigated oxidative stress injury by alleviating the levels of reactive oxygen species (ROS) and malondialdehyde (MDA) while increasing antioxidant enzymes. Furthermore, TAX decreased the apoptosis of the aging brain by regulating the phosphorylation levels of phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT), and activating nuclear factor-erythroid 2-related factor 2 (Nrf2), nuclear heme oxygenase-1 (HO-1), and NADH dehydrogenase quinone 1 (NQO1) to maximally moderate the oxidative stress injury that occurred after d -Gal induction. In addition, 16S rDNA analysis revealed that TAX treatment decelerated the d -gal-induced aging process by regulating the composition of the intestinal flora and abundance of beneficial bacteria, including Enterorhabdus, Clostridium, Bifidobacterium, and Parvibacter . In conclusion, the results of this study demonstrated that TAX alleviated oxidative stress injury in mice aged by d -Gal and also confirmed that TAX improved the aging process by regulating intestinal microbes, which provides the possibility of prevention and treatment for aging and metabolic disorders through the potential food health factors.